Implication of Fatty Acids and Seed Dormancy in a New Screening Procedure for Cold Tolerance in Rice - Majumder, M.K.; Seshu, D.V.; Shenoy, V.V. (Wiley, 1989)
Developing a suitable screening technique to identify appropriate genetic donors, and segregants is a requisite to the successful incorporation of cold tolerance into high yielding, semidwarf rice (Oryza sativa L.) cultivars. This study investigated relationships between cold tolerance and unsaturated fatty acids (USFAs); between seed dormancy and short‐chain saturated fatty acids (SCSFAs), specifically, nonanoic acid (C9); and between cold tolerance and seed dormancy in rice. The cold‐tolerant cultivars accumulated higher quantities of USFAs in 40‐d‐old leaves and mature grains compared to the cold‐susceptible cultivars under the optimum (29/21 °C day/night) and the low (22/18 °C) temperatures in the phytotron. The tolerant cultivars also showed a null allelic situation at the esterase 2 locus (20). The susceptible and the less tolerant cultivars had either the esterase 21 or the esterase 22 allele. The esterase 21 and the esterase 22 allozymes utilized the choline ester precursors of USFAs to liberate free USFAs, reportedly the precursors of the SCSFAs in plants. The strongly dormant cultivars had the esterase 21 allele and accumulated higher levels of SCSFAs in the mature seeds compared to the nondormant cultivars. Nonanoic acid was the most effective seed dormancy imposer of the four SCSFAs tested. For the artificial imposition of dormancy, the seeds of cold‐tolerant cultivars needed more nonanoic acid than the cold‐susceptible cultivars. Thus, based on germination response to nonanoic acid and the esterase 2 allozyme pattern, a reliable two‐tier screening technique has been developed to identify cold‐tolerant rice cultivars.